Situation Report: Romania, 30 March 1983 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
An information bulletin produced by Radio Free Europe/Radio Liberty based on extensive monitoring of communist bloc news outlets and primarily intended for internal circulation. Pieces were generally contributed by the staff of the research and analysis departments and treated current affairs in the region. Romania and the Next CMEA Summit Meeting Bucharest's Reaction to the West German Elections Romania and the Nonaligned Summit in New Dehli [Delhi] Animal Breeding Sector Criticized Reorganization of Forestry Film Polemics with Hungary